PERAN STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN MINAT BELI MASYARAKAT TERHADAP PRODUK M-150 DI SUZUYA SUPERMARKET KOTA MEDAN - David Cardona; Irene Silviani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
In accordance with Kotler & Armstrong's theory, explaining integrated marketing communication can form a strong identity of a brand to tie together and strengthen the message and image of a company, to produce consistency for a communication budget to be more effective, communication is getting better and its impact is an increase in sales. This study aims at determining the role of marketing communication strategies in increasing public interest in buying M-150 Products at Suzuya Supermarket, Medan City. The method used is descriptive qualitative, to explain and describe the phenomena occurred. The results of the study show that the sale of M-150 Products at SUZUYA Supermarket dropped sharply because it did not use Communications Strategy. This affects the buying interest of people who are less familiar with the benefits and uses of the product.